Real-world response of patients with locally advanced pancreatic adenocarcinoma to high intensity focused ultrasound treatment: a single-center, observational study in China - Wu, Congye; Wu, Xinmei; Zhao, Huanyu; Gu, Dongying; Wei, Xiaowei; Tang, Cuiju; Chen, Jinfei (Translational Cancer Research; Vol 7, No 6 (December 30, 2018): Translational Cancer Research, 2018)
Background: The purpose of this study was to evaluate the feasibility of high intensity focused ultrasound (HIFU) ablation for tumor response and local control in selected patients with unresectable locally advanced pancreatic cancer (LAPC). Methods: Forty-six malignant cases of unresectable pancreatic cancer were treated in our center from February 2013 to December 2016, and were included in this analysis. Response was determined with the response evaluation criteria in solid tumors (RECIST v1.1). Overall survival (OS), including 12-month survival rates and complications were also recorded and analyzed. Results: Clinical responses (ablation obtained) were observed in 43.48% of the cases, and disease control [complete response (CR), partial response (PR), and stable disease (SD)] was observed in 43 (93.48%) of 46 cases. Stratified analyses suggested that receiving radiotherapy per-HIFU might affect the response rate. Median OS was 9.7 months, with 95% CI, 7.9–13.2 months. The 1-year survival rate was estimated to be 46.69% (95% CI, 31.71–60.34%). Age